Airfield and Highway Pavements 2019. selected papers from the International Airfield and Highway Pavements Conference 2019, July 21-24, 2019, Chicago, Illinois - Al-Qadi, Imad L.; Ozer, Hasan; Loizos, Andreas; Murrell, Scott (American Society of Civil Engineers, 2019)
Contains 44 peer-reviewed papers on the design, construction, condition evaluation, and management of airfield and highway pavements . Topics include: mechanistic-empirical pavement design methods; advanced modeling techniques for pavements; construction specifications and quality monitoring; accelerated pavement testing; rehabilitation and preservation methods; pavement condition evaluation; and network-level management of pavements. This proceedings will be of interest to transportation infrastructure researchers, consultants, designers, project/construction managers, and contractors from around the world.